2009
DOI: 10.1073/pnas.0907941106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the lethal phage pinhole

Abstract: Perhaps the simplest of biological timing systems, bacteriophage holins accumulate during the phage morphogenesis period and then trigger to permeabilize the cytoplasmic membrane with lethal holes; thus, terminating the infection cycle. Canonical holins form very large holes that allow nonspecific release of fully-folded proteins, but a recently discovered class of holins, the pinholins, make much smaller holes, or pinholes, that serve only to depolarize the membrane. Here, we interrogate the structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
185
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(200 citation statements)
references
References 36 publications
13
185
2
Order By: Relevance
“…Previous studies have shown that the holin from lambda bacteriophage 21 has two TMDs, and that TMD 1 is dispensable for pore formation and lysis (Pang et al, 2009). However, our results showed that both TMD 1 and TMD 2 of HolGH15 are indispensable for the function of the full-length protein.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that the holin from lambda bacteriophage 21 has two TMDs, and that TMD 1 is dispensable for pore formation and lysis (Pang et al, 2009). However, our results showed that both TMD 1 and TMD 2 of HolGH15 are indispensable for the function of the full-length protein.…”
Section: Discussioncontrasting
confidence: 65%
“…The typical holin forms very large pores (large enough for 500 kDa proteins) that allow the non-specific release of endolysins and other proteins into the cytoplasm (Bläsi & Young, 1996;Wang et al, 2003). However, the holin protein of lambda phage 21 forms pinholes that only depolarize the membrane (Pang et al, 2009(Pang et al, , 2010a(Pang et al, , b, 2013. Holins are also important for many activities, such as classification, gene transfer (Lang & Beatty, 2001), biofilm formation (Ranjit et al, 2011) and biotechnology material production (Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the behavior of purified S 21 68 and S105 in the nonionic detergent dodecylmaltoside supports the notion that the canonical holin has much more scope for protein-protein interactions (20). S105 was found to form highly oligomeric ring structures estimated to contain >70 molecules, whereas S 21 68 forms a heptameric homooligomer in dodecylmaltoside (4).…”
Section: Discussionsupporting
confidence: 59%
“…The results of a combined biochemical, genetic, ultrastructural, and computational approach indicate that the prototype pinholin, S 21 68 ( Fig. 1 A and B), of lambdoid phage 21 of Escherichia coli forms heptamers with a central lumen <2 nm in diameter (4), too small to allow the passage of endolysin (5). Phages using pinholins, therefore, require a distinct class of muralytic enzymes called the signal anchor release (SAR) endolysins, which are exported in a membrane-tethered enzymatically inactive form during the latent period.…”
mentioning
confidence: 99%
“…This would undoubtedly kill the cell. Indeed, b-barrel toxins, such as alpha-haemolysin, as well as many a-helical antimicrobial peptides use this 'hole poking' mechanism to kill foreign cells [6][7][8].…”
Section: Introduction: the Challenges Of Unfolded Outer Membrane Protmentioning
confidence: 99%